Secular trends of physical fitness in elite youth alpine skiers: An analysis of performance in 2013 and 2023 - Pavlovic, L.; Stamenkovic, S.; Krajncic, T.; Lešnik, B. (Facta Universitatis: Series Physical Education and Sport, 2025)
This study compares physical fitness performance and determined secular trends in elite youth alpine skiers tested in 2013 and 2023. One hundred forty elite youth alpine skiers, aged 12 or 13 years, participated in this study. 30 boys and 25 girls were tested (n = 55) in 2013, whereas in 2023 the sample included 47 boys and 38 girls (n = 85). Elite male youth skiers showed a significant change only in speed performance over 20 meters (p < 0.05). In contrast, female skiers demonstrated significant improvements in explosive power, anaerobic performance and speed (all p < 0.05). Over the last decade, elite U12-U13 alpine skiers have maintained or modestly increased most key fitness attributes, with girls showing wider-ranging improvements than boys.